Penguatan Pengalaman Keagamaan Di Sekolah - Zamzami, M. Cholid (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
This research is the implementation of Islamic education in instilling religious consciousness. This research is descriptive-qualitative. The data from a school principal, teachers, and students were collected through observation, interview, and documentation. The data were analyzed usingsuch techniques as the reduction, display and verification of data. The implementation of religious consciousness and reinforcement of Islamic education in this kind of activity was carried out in structured learning in classroom, and extra-curricular activities outside class, established by teachers through instilling religious values, giving a role model, and habituation. The model of reinforcement is; fist) verbal reinforcement that’s praise, second) giving reward to the student that finish his duty, third) punishment for breaking the rules; fourth) religious activities and prayingfor created religious culture at school. Student’s religious consciousness can be seen from school culture manifested in such activities as Zhuhr prayer by jama’ah, Friday’s charity, respect for teacher and friends, student’s responsibility, student’s avoidance of negative interactionswhich can harm themselves and their learning achievements.Keyword; reinforment of Islamic education, religious consciousness,